Effect of three final irrigation protocols on the smear layer removal from the middle third of endodontically treated teeth: A qualitative analysis - Miranda, Jean Soares [UNESP]; Marques, Érico de Almeida; de Landa, Fabiano Vieira; Leite, Anamaria Pessôa Pereira; Leite, Fabíola Pessôa Pereira (Dental Press International, 2017)
Objective: this study evaluated by scanning electron microscopy (SEM) the sealer capacity of dentinal tubules of teeth treated endodontically using different chelating solutions. Materials and Methods: The root canals were irrigated with 2.5% sodium hypochlorite (NaOCl), replaced every instrument and filled. The auxiliary solutions used with a passive ultrasonic irrigation (PUI) for 1 minute were: 70% ethanol (control); 10% citric acid; 17% EDTA; and 0,2% chitosan. The roots were split lengthwise into two parts and samples were taken for analysis in a scanning electron microscope to obtain photomicrographs for the qualitative assessment. Results: 17% EDTA solution and 10% citric acid removed the smear layer similar to each other. The 0.2% chitosan solution removed the smear layer partially, with lower efficacy than 17% EDTA solution and 10% citric acid. Conclusion: There were a greater removal of smear layer with use of 17% EDTA, followed by 10% citric acid, 0,2% chitosan and 70% alcohol.
Keywords: Chelating agents; Chitosan; Endodontics; Nonvital; Tooth